2014
DOI: 10.11118/actaun201462030517
|View full text |Cite
|
Sign up to set email alerts
|

From Wasted Land to Megawatts: How to Convert Brownfields Into Solar Power Plants (the Case of the Czech Republic)

Abstract: This article deals with the issue of brownfi eld redevelopment for the needs of solar energy projects from diff erent perspectives. Attention is fi rst paid to a brief characterisation of the data and information available both for brownfi elds and for solar energy projects in the Czech Republic. Then there is description from the most important results of GIS analysis, which (based on a comparison of aerial images from diff erent years) identifi ed the previous uses at the 127 solar power plants with an outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…They are, however, highly dependent on its technical state, location or health and safety connected issues (Haase, 2008). The temporary use of brownfields might be linked to an organisation of cultural or sport events (Andres, 2011), the use of brownfields for renewable energy production such as location of solar plant or growing of biomass (Adelaja et al, 2010;Evangelou et al, 2012;Klusacek et al, 2014), the projects of urban agriculture (Duzi et al, 2017;Koopmans et al, 2017;LaCroix, 2010) or the use of brownfields for leisure time of the local population or tourism (Zhang and Klenosky, 2016).…”
Section: The Need For "Sustainable" Regeneration Of Brownfieldsmentioning
confidence: 99%
“…They are, however, highly dependent on its technical state, location or health and safety connected issues (Haase, 2008). The temporary use of brownfields might be linked to an organisation of cultural or sport events (Andres, 2011), the use of brownfields for renewable energy production such as location of solar plant or growing of biomass (Adelaja et al, 2010;Evangelou et al, 2012;Klusacek et al, 2014), the projects of urban agriculture (Duzi et al, 2017;Koopmans et al, 2017;LaCroix, 2010) or the use of brownfields for leisure time of the local population or tourism (Zhang and Klenosky, 2016).…”
Section: The Need For "Sustainable" Regeneration Of Brownfieldsmentioning
confidence: 99%
“…The relevance of the PV and wind energy sub-sectors, in terms of job creation, has been lower for the Czech Republic. This reflects both biophysical suitability (a landlocked country with limited sun and wind but significant agricultural potential [66] and [67]) and the nature of these sub-sectors where most jobs are in the development and installation phase and relatively few jobs are required for maintenance. Renewable energy policy requires large investments and financial incentives, which should be framed and spent wisely.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…A major increase of acreage is linked to the installation of large-scale on-ground photovoltaic power plants (an increase of 5.114 areas, thus, for example, some 87% of new areas of agricultural premises in České Budějovice SD). This increase of non-agricultural use is most frequently seen at the expense of arable land immediately attached to the original agricultural premises (Klusáček et al, 2014). Only in two cases (covering a total acreage of 245 ares), have we found that pre-1989 agricultural premises were demolished and a photovoltaic power plant was developed.…”
Section: Discussionmentioning
confidence: 89%